EMPOWERMENT OF ISLAMIC YOUTH ORGANIZATIONS IN TACKLING ADOLESCENT SOCIAL BEHAVIOR THROUGH LEADERSHIP DEVELOPMENT AND CREATIVITY IN KEDUNG JAYA BEKASI VILLAGE - Hunaidah, Hunaidah; Akbar, M. Azril; Yanuar, Fitra Arya; Juarsih, Juarsih; Mustawa, Nadiya (LPPM Univ. Ibn Khaldun Bogor, 2024)
This research aims to explain (1) the implementation of overcoming adolescent social behavior through leadership training and creative economy as well as assistance in religious education activities carried out in Kedung Jaya Village, Babelan District, Bekasi Regency, West Java, (2) the participation of Islamic youth involved in the implementation of behavioral control. Social media for adolescents in Kedung Jaya Village, Babelan District, Bekasi Regency, West Java. One of the organizations that exist in rural areas is an Islamic youth organization, both under the management of a mosque and an independent organization under private management engaged in social and religious fields that require a touch of academic (touching of academic) in running programs to anticipate behavior. of teenagers who are inappropriate or who can harm socially both individuals and groups. The youth group in the community structure is significant in community empowerment. Teenagers are part of a group of people who are in the identity versus identity phase and are undergoing adolescence (puberty) which is very easy to accept and absorb what is happening around them by prioritizing the aspect of ego (egocentricity) in behavior or action. Fast-paced social changes have a significant impact on changes in adolescent behavior both in terms of behavior and mindset. The youth empowerment that we do in tackling the social behavior of youth based on Islamic youth organizations is carried out through leadership and creativity training activities that aim to motivate and inspire rural youth to be more efficient and effective in facing various global changes more optimistically and confidently through the provision of the knowledge and skills provided by STAI Attaqwa Bekasi students in a research-based KKN program located in the Babelan sub-district. The target orientation in this activity is teenagers who are active in various Islamic youth organizations in the village of Kedung Supervisor. The method we use in this activity is the PAR (Participatory Action Research) method, namely by involving youth to participate in the management of the training program. Data reduction is done through FGD (forum group discussion) and the resulting product. Leadership training and creativity in the use of ginger plants (ginger plant) in healthy food, and waste cooking oil used as aroma therapy candles as well as assistance in religious education activities that we do during research-based KKN are incentives for teenagers to have insight and real skills to be able to maintain self-defense and be able to control oneself from behaviors that can harm oneself and others. And can inspire young Islamic organizations to take better care of themselves, and be more creative and innovative in utilizing the materials around them to make them more economically valuable as the goal of maqoshid al-syari'ah which must be implemented in everyday life as part of the reconstruction of Islamic education.